An Apology: Heartfelt Reflections on the Passing of a Legendary Blackamerican Muslim leader (American Journal of Islam and Society, 2008)
On September 11th, 2008, while countless American flags whipped inthe wind and the television and radio waves were dominated by remembrances,recordings, and stories about the terror attacks of seven years ago,I attended the funeral of ImamW.D.Mohammed (may God be pleased withhim). Forme, it was a somber day, but I found myselfmostly lost in thought:about African-American Muslim communities, about the challenges aheadin American Muslim institution-building, and about the future of Islam inAmerica. If you don’t know who ImamWDMwas, you should look him up.The Sufis say: “The true sage belongs to his era.” And of the many giftsgiven to ImamWDM by God, perhaps the most obvious and beneficial onewas the Imam’s profound understanding of the principles of religion, and hisadeptness at intelligently applying those Islamic principles in a socially andculturally appropriate manner befitting the everyday lives of his NorthAmerican followers. While carefully respecting sound, traditional jurisprudentialmethodologies of the Islamic religion, and the collective religioushistory and time-honored scholarship of classical Islam, he promulgated creativeideas and dynamic teachings across many domains of human endeavor,including theology, law, spirituality and even ethics and aesthetics, thattogether articulated a vision for a quintessentially “American Muslim” cultural identity. And he did all of this before anyone else, with quiet strengthand unending humility – a true sage indeed ...